On the real effects of private equity investment: evidence from new business creation - Alexander Popov; Peter Roosenboom (European Central Bank (ECB), 2009)
Using a comprehensive database of European firms, we study how private equity affects the rate of firm entry. We find that private equity investment benefits new business incorporation, especially in industries with naturally higher entry rates and R&D intensity. A two standard deviation increase in private equity investment explains as much as 5.5% of the variation in entry between high-entry and low-entry industries. We address endogeneity by exploiting data on laws that regulate private equity investments by pension funds. Our results hold when we correct for barriers to entry, general access to credit, protection of intellectual property, and labor regulations.
Keywords: G24; L26; M13; 330; firm entry; private equity; Venture Capital; Private Equity; Risikokapital; Unternehmensgründung; Markteintritt; Innovation; EU-Staaten